TRACE METAL CONCENTRATION IN THE SURFACE SEDIMENTS OF PAKA MANGROVE FORESTS, TERENGGANU, MALAYSIA - B.Y, Kamaruzzaman; M.C, Ong; K.Y.S, Willison (Malaysian Journal of Science, 2004)
Surface sediment samples ftom 2 transects (20 stations) of mangrove forest of Paka were analyzed for the concentrations of Mn, Cu, Zn and Pb. In this study, the average concentrations of Mn, Cu, Zn and Pb were 112.4 ± 3.6 µ/g dry weight, 18.1 ± 0.91 µ/g dry weight, 44.9 ± 0.22 µ/g dry weight and 24.1 ± 0.36 µ/g dry weight, respectively. The calculated enrichment factors (EF) obtained for Cu, Zn and Pb can be considered to have the terigeneous in sources while Mn, which has slightly higher value, was probably influenced by anthropogenic input. The concentration of metal especially for Mn and Pb, increased with the decrease of mean size particle, suggesting their association with the fine &action of the sediments.